2020
DOI: 10.1177/1078087420964254
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and Austerity: How Did the Great Recession Affect Municipal Economic Development Policy?

Abstract: In addition to cuts in social programs, the Great Recession also affected government expenditures once considered less vulnerable to austerity, such as economic development. Using a comparative case study approach, we examine economic development policies and practices in two cities, sampled for similar economic and fiscal conditions: Fresno, California and Milwaukee, Wisconsin. We find that declining state support and local autonomy weakened the municipal economic development function while leaving entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Likewise, the Great Recession of 2007 to 2009 resulted in decreased consumer demand triggered by a shortfall in wages, increased unemployment, and widespread foreclosures. In the aftermath, many local governments were impacted by a severe reduction in property taxes and suppressed consumer demand ( Hinkley and Weber 2021 ).…”
Section: Economic Development Policies Used During the Crisis: The Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the Great Recession of 2007 to 2009 resulted in decreased consumer demand triggered by a shortfall in wages, increased unemployment, and widespread foreclosures. In the aftermath, many local governments were impacted by a severe reduction in property taxes and suppressed consumer demand ( Hinkley and Weber 2021 ).…”
Section: Economic Development Policies Used During the Crisis: The Ca...mentioning
confidence: 99%
“…Opp, Osgood and Rugeley (2014) found that the emphasis was on visible and salient development-oriented policies to signal those efforts were being made during the Great Recession. Hinkley and Weber (2021) found in a recent analysis of the Great Recession's impact on economic development and fiscal planning in Fresno and Milwaukee that Milwaukee responded by increasing their usage of Tax Increment Financing (a supply-side strategy) and both Fresno and Milwaukee increased regional economic development efforts. In other instances, local governments responded by diversifying their industrial profile by focusing on industries that were more resilient and shock-resistant, like high-tech and biomedical research ( Cowell, Gainsborough and Lowe 2016 ; Deller and Watson 2016 ).…”
Section: Economic Development Policies Used During the Crisis: The Ca...mentioning
confidence: 99%
“…Hal tersebut juga dilakukan oleh Pemerintah Kota di Swiss dan pemerintah lokal di Amerika Serikat (Pemerintah Fresno dan Milwaukee) yang menerapkan langkah-langkah penghematan pengeluaran untuk mengatasi defisit anggaran melalui pembatasan program pembangunan ekonomi dan rescaling insentif. (Ladner & Soguel, 2015;Hinkley & Weber, 2021). Menurut Jimenez (2018), penghematan fiskal yang dikombinasikan dengan perencanaan rasional saat krisis dapat memperbaiki kesehatan fiskal dan memulihkan ekonomi.…”
Section: Hasil Dan Pembahasanunclassified
“…The Great Recession resulted in varying effects (usually declines) in revenue, budgets, employment, investment, and economic development activities in states and local governments of the United States. Some of the most affected sectors of the economy were government, real estate, and construction, and in some areas building permits declined considerably ( Bardhan and Walker, 2011 ; Hinkley and Weber, 2021 ). The selected cities are quite different concerning their position within the geography of the country, local climatic conditions, and their history of development.…”
Section: Introductionmentioning
confidence: 99%